Sensory Nudges: The Influences of Environmental Contexts on Consumers’ Sensory Perception, Emotional Responses, and Behaviors toward Foods and Beverages - Seo, Han-Seok (Foods, 2020)
Food products with highly acceptable flavors are not always successful in the marketplace. Sales of identical food products sold in two different stores often differ. Patrons’ choices of specific menu items vary depending on menu designs at restaurants. Such examples suggest that consumer behavior related to eating, preparing, or purchasing foods and beverages is typically complex, dynamic, and sensitive. There is a growing body of evidence that environmental cues surrounding foods and beverages can modulate consumer perception and behavior in the context of eating and drinking. In light of increasing interest in environmental cues, this Special Issue was designed to introduce recent research that highlights how sensory cues derived from environmental cues can modulate consumer perceptions, emotional responses, and behavior related to foods and beverages. The eleven articles addressed in this Special Issue provide informative and insightful findings that may be applied to a wide range of food-related sites, including grocery stores, retail markets, restaurants, dining facilities, and public dining areas. The findings from these articles also suggest that product developers, sensory professionals, retailers, marketers, and business owners should consider not only sensory aspects of food products, but also sensory cues derived from surrounding contexts to better understand consumer perception, acceptability, and behavior toward their food products.